From human rights to rights of mother Earth a biocentrist approach - Galárraga Santiago Vallejo (Szegedi Jogász Doktorandusz Konferenciák, 2018)
The present article comprises the analysis of biocentric principles, which currently support the theories promoting the recognition of Nature, as a subject of law and a holder of rights, emphasizing the legislative challenges regarding their extension. It also includes a brief critical review of the most remarkable international binding instruments, presently in force, that rule the prevailing doctrine of the human right to a healthy environment, in order to outline a later transition to rights of nature.